HAMBATAN BELAJAR MAHASISWA PRODI D3 TATA BOGA PADA MATA KULIAH MANAJEMEN USAHA BOGA CATERING DI JURUSAN KESEJAHTERAAN KELUARGA FAKULTAS TEKNIK UNP - Ramadhani, Nuzli; Syarif, Wirnelis; Chair, Ira Meirina (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2013)
This study aims to determine the barriers students Prodi D3 Catering course on Business Management Catering both internal and external barriers. Informants in this study were students in entry 2008 and 2010 who have taken courses Unread Catering Management Catering and 1 person supervising teacher. Data collection techniques used observation, interviews, and documentation. The results, showed that the presence of obstacles on this course. The internal resistance is seen at the student motivation to achieve the target of practice on the course Catering and Hospitality Business Management is also the motivation to seek consumer does not look like distributing flyers and pamphlets stuck. 2). External barriers are seen supporting infrastructure courses namely Business Management Catering workshop for practice. Should be workshops for the implementation of this course is devoted practice that the practice can run smoothly. Â Kata kunci: Hambatan Belajar, Manajemen Usaha Boga Catering, Prodi D3Â Tata Boga